Quranic Tolerance Moderation To Counter Radicalism for Kicking Sesajen in Mount Semeru: A Case Study on Kompastv.com Youtube Channel - Basid, Abdul; Ma'arif, A. Samsul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to analyze the contribution of Tawhid verses to the phenomenon of kicking Sesajen and identify the objectives, benefits, methods, and results of the study in a case study on Kompas TV.Com. The phenomenon of kicking Sesajen is a controversial behavior in society. A qualitative approach is used in this research with content analysis to analyze the relevant content related to the phenomenon on the Kompas TV.Com platform. The main objective of this research is to understand the contribution of Tawhid verses to the phenomenon of kicking Sesajen. The benefit of this research is to provide a deeper understanding of the relationship between the concept of Tawhid in Islam and the behavior of kicking Sesajen. The research method involves analyzing the content of articles, videos, and comments on the phenomenon on Kompas TV.Com. The study results indicate that Tawhid verses significantly contribute to the phenomenon of kicking Sesajen. Tawhid verses emphasize the oneness of Allah and the prohibition of worshiping other than Him, as well as not giving a negative impression on the followers of other religions by not insulting their worship. This research also reveals that through the Kompas TV.Com platform, the community can participate in commenting on this phenomenon and gain a broader understanding of the implications of the Qur'an for social behavior. Good customs will not contradict the goals of religion but instead provide meaning that supports sustainable cultural values. Therefore, we need to maintain a balance between customs and religion. Religion cannot spread without the presence of culture; likewise, culture will lose its direction without the guidance of religion.